The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12885-015-1563-8
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis on MR images helps predicting non-response to NAC in breast cancer

Abstract: BackgroundTo assess the performance of a predictive model of non-response to neoadjuvant chemotherapy (NAC) in patients with breast cancer based on texture, kinetic, and BI-RADS parameters measured from dynamic MRI.MethodsSixty-nine patients with invasive ductal carcinoma of the breast who underwent pre-treatment MRI were studied. Morphological parameters and biological markers were measured. Pathological complete response was defined as the absence of invasive and in situ cancer in breast and nodes. Pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 60 publications
0
65
1
Order By: Relevance
“…One trial reported up to 23% of patients with primary operable breast cancer can have breast conserving surgery instead of mastectomy if treated with neoadjuvant therapy 7 . However, response rates to NAT vary among patients and have been shown to depend on subtype 816 . In fact, up to 30% of patients may not respond to NAT 17 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One trial reported up to 23% of patients with primary operable breast cancer can have breast conserving surgery instead of mastectomy if treated with neoadjuvant therapy 7 . However, response rates to NAT vary among patients and have been shown to depend on subtype 816 . In fact, up to 30% of patients may not respond to NAT 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, up to 30% of patients may not respond to NAT 17 . These patients incur toxicities and costs of treatment but gain proportionally less benefit 7,8 . Identifying a method to predict which breast cancer patients will achieve pCR and which will have residual invasive disease (RD) following NAT would allow for improved stratification of patients to more appropriate treatment regimens 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative radiomic features extracted from breast dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) have been shown to be associated with genetic expression profiles in breast cancer . Radiomic breast MRI features have also been shown to be predictive of the response of neoadjuvant chemotherapy, recurrence risk, and recurrence‐free survival for breast cancer patients …”
mentioning
confidence: 99%
“…Already the first valuable study showed a very good correlation of two different PET parameters with the final pathological response in primary tumors receiving neoadjuvant chemotherapy [18]. Also, for dedicated breast MRI, different parameters (diffusion-weighted imaging, perfusion changes, or functional tumor volume) were evaluated and have been shown to be of value for response assessment in neoadjuvant chemotherapy [21][22][23][24].…”
mentioning
confidence: 99%